2018
DOI: 10.1016/j.still.2018.02.007
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of soil structure through organic crop management, conservation tillage and grass-clover ley

Abstract: Conventional tillage is a widespread soil management practice that controls weeds and promotes nutrient mineralization at the expense of a degraded soil structure and soil carbon (C) loss. Although C dynamics and soil structure are widely recognized as pivotal to essential environmental and crop-related agroecosystem processes such as belowground C storage and crop root establishment, there is still a need to evaluate cropping practices most favorable for soil structure. For example, the effects on soil struct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
40
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(46 citation statements)
references
References 96 publications
6
40
0
Order By: Relevance
“…Moreover, SOM increased considerably in FAST from 2014 to 2017 and was the highest in O-RT in both years. This finding could be explained by the 2year grass-clover ley that was grown between winter wheat and maize within the FAST rotation and is known to increase SOM in agricultural soils (Loaiza Puerta et al 2018). The increased SOM content in the topsoil layer in O-RT might be attributed to the combined effect of organic fertilization and reduced tillage intensity.…”
Section: The Effect Of Organic Farming On Soil Erosionmentioning
confidence: 95%
See 1 more Smart Citation
“…Moreover, SOM increased considerably in FAST from 2014 to 2017 and was the highest in O-RT in both years. This finding could be explained by the 2year grass-clover ley that was grown between winter wheat and maize within the FAST rotation and is known to increase SOM in agricultural soils (Loaiza Puerta et al 2018). The increased SOM content in the topsoil layer in O-RT might be attributed to the combined effect of organic fertilization and reduced tillage intensity.…”
Section: The Effect Of Organic Farming On Soil Erosionmentioning
confidence: 95%
“…Loaiza Puerta et al (2018) reported that organic management together with reduced tillage significantly improved the soil structure in the FAST experiment. Conservation tillage can promote aggregation of microaggregates into macroaggregates compared to intensive tillage (Six et al 2000b), and macroaggregate turnover is lower under reduced tillage (Six et al 2000a).…”
Section: The Effect Of Reduced Tillage On Soil Erosion In Organic Farmentioning
confidence: 98%
“…Under mineral fertilization conditions, greenhouse systems are recognized as an intensive agricultural practice that leads to land degradation (Yang, Hao, Li, & Li, ), while the organic greenhouse system had a significant positive effect on soil pores, leading to improved crop yield and soil quality (Schrama et al., ). We believe that the principal factor explaining this pattern is organic fertilization, which is regarded as a traditional method for improving soil porosity and enhancing water–air transmission (Conacher & Conacher, ; Loaiza Puerta et al., ). A 37‐year field experiment on the effects of soil properties in Switzerland also showed that organic management supplied a 25 to 80% greater C input to the soil than did mineral fertilization and resulted in better physical properties (Maltas et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Similar results were obtained by Papadopoulos, Bird, Whitmore, and Mooney () with X‐ray computed tomography (CT) scanning in the UK. In addition, several researchers have examined the effect of organic fertilization on soil pores under other beneficial modes of tillage (Cogger, Bary, Myhre, Fortuna, & Collins, ; Loaiza Puerta, Pujol Pereira, Wittwer, van der Heijden, & Six, ). For example, Loaiza Puerta et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation